Análisis de las estrategias de marketing para la comercialización de productos agrícolas en la Hacienda Bananera Erikita del cantón Puebloviejo periodo 2019-2020 - Mora Fierro, Meily Melina (2021)
The use of marketing strategies is one of the activities that promote the position of companies in the market, due to this, the study is developed with the aim of analyzing and identifying the marketing strategies implemented by the Erikita banana farm, while The research methodology that supports the treatment of information corresponds to the descriptive, analytical and bibliographic method as well as the type of research according to its data, this being qualitative through the interview technique and applied through the instrument, interview guide, which will allow to know the point of view of the administrators of the company with respect to the subject, in accordance with the line of research information and communication systems and entrepreneurship and innovation and the respective marketing and commercialization sub-line. Therefore, it was identified that the company presents problems related to marketing strategies such as: non-existence of a specialized department, they do not have technical professionals in the area, they do not have an established strategic plan, they develop deficient advertising actions, they do not have social networks, the web portal maintains only informative data in a generalized way and the owners consider it is not necessary to carry out management in relation to the promotion of products that affect decision-making in relation to the decomposition of the stored product due to the lack of buyers.